Assessment of bracket surface morphology and dimensional change - Pillai Devu Radhakrishnan; N K Sapna Varma; V V Ajith (Wolters Kluwer Medknow Publications, 2017)
Objective: The objective of this study was to compare the surface morphology and dimensional stability of the bracket slot at the onset of treatment and after 12 months of intraoral exposure. The study also compared the amount of calcium at the bracket base which indicates enamel loss among the three orthodontic brackets following debonding after 12 months of intraoral exposure. Materials and Methods: The sample consisted of 60 (0.022" MBT) canine brackets. They were divided into three groups: self-ligating, ceramic bracket with metal slot, and stainless steel (SS) brackets. The slot dimensions, micromorphologic characteristics of as-received and retrieved brackets were measured with a stereomicroscope and scanning electron microscope (SEM), respectively. The amount of calcium at the bracket base which indicates enamel damage was quantified using energy-dispersive X-ray spectrometry (EDX). Results: The results showed statistically significant alterations (P < 0.05) in the right vertical dimension, internal tie wing width (cervical), right and left depth of the slot (Kruskal-Wallis test). Multiple comparison using Mann-Whitney test showed that ceramic brackets underwent (P < 0.05) minimal alterations in the right vertical dimension, internal tie wing width (cervical), right and left depth of the slot (0.01 mm, −0.003 mm, 0.006 mm, −0.002 mm, respectively) when compared with the changes seen in SS and self-ligating brackets. SEM analysis revealed an increase in the surface roughness of ceramic with metal slot brackets and self-ligating bracket showed the least irregularity. The presence of calcium was noted on all evaluated brackets under EDX, but ceramic with metal slot brackets showed a significantly greater amount of enamel loss (P = 0.001). Conclusion: Ceramic brackets were found to be dimensionally stable when compared to SS and self-ligating. Self-ligating bracket showed minimal surface irregularity. Ceramic with metal slot brackets showed a greater amount of enamel loss following debonding.